2019
DOI: 10.1097/ccm.0000000000003667
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Advanced Practice Provider in Adult Critical Care: A Systematic Review and Meta-Analysis*

Abstract: Objectives: To evaluate the effects on quality and efficiency of implementation of the advanced practice provider in critical care. Data Sources: PubMed, Embase, The Cochrane Library, and CINAHL were used to extract articles regarding advanced practice providers in critical care. Study Selection: Articles were selected when reporting a comparison between advanced practice providers and physician resident/fel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 44 publications
4
30
0
Order By: Relevance
“…One systematic review of 18 studies of APPs in acute care (15), a systematic review of 15 studies of advanced practice nursing roles in emergency and critical care settings (16), a systematic review of 29 studies of APP care on surgical services (17), a systematic review of 14 studies of NP impact on cost, quality of care, satisfaction and wait times in ED settings (18), a literature review of 47 studies on NP care on critical care services (19), a narrative review of 29 studies related to PA satisfaction (20), a literature review of 12 studies on NP use and intensivist staffing (21), a literature review of five studies focused on APP care for ICU patients (22), a systematic review of 30 studies on the impact of APP care for adult critical care patients with a meta-analysis of eight studies (23), and 44 individual studies were identified. The studies addressed a variety of APP models of care including 24/7 ICU coverage (24), and specialty practice roles including cardiovascular surgery (25–28), neuroscience (29, 30), trauma care (3139), pediatric critical care (4044), oncology care (45, 46), surgical services (17, 47), ED settings (16, 19), orthopedics (48), stroke care (30), heart failure care (49), burn care (15), aneurysmal subarachnoid hemorrhage care (50), and palliative care (51), among other areas of specialty care.…”
Section: Resultsmentioning
confidence: 99%
“…One systematic review of 18 studies of APPs in acute care (15), a systematic review of 15 studies of advanced practice nursing roles in emergency and critical care settings (16), a systematic review of 29 studies of APP care on surgical services (17), a systematic review of 14 studies of NP impact on cost, quality of care, satisfaction and wait times in ED settings (18), a literature review of 47 studies on NP care on critical care services (19), a narrative review of 29 studies related to PA satisfaction (20), a literature review of 12 studies on NP use and intensivist staffing (21), a literature review of five studies focused on APP care for ICU patients (22), a systematic review of 30 studies on the impact of APP care for adult critical care patients with a meta-analysis of eight studies (23), and 44 individual studies were identified. The studies addressed a variety of APP models of care including 24/7 ICU coverage (24), and specialty practice roles including cardiovascular surgery (25–28), neuroscience (29, 30), trauma care (3139), pediatric critical care (4044), oncology care (45, 46), surgical services (17, 47), ED settings (16, 19), orthopedics (48), stroke care (30), heart failure care (49), burn care (15), aneurysmal subarachnoid hemorrhage care (50), and palliative care (51), among other areas of specialty care.…”
Section: Resultsmentioning
confidence: 99%
“…Recent research on APPs in critical care often focused on the evaluation of clinical patient-related outcomes and performances of these APPs in conjunction with a coordinating medical specialist. (2)(3)(4) In this study the non-technical skills of APPs and residents as leaders of a RRT were assessed without this additional consultation. APPs performed better than residents in several subcategories and omitted overall less predefined critical steps.…”
Section: Discussionmentioning
confidence: 99%
“…Literature reviews that comprise more recent studies on APP impact emphasize improvement in the patient care experience and outcomes rather than performing tasks to ease resident workload as motivating factors for their inclusion in the acute care staffing model. 11,12,14,22 The survey question regarding APP participation in research or QI suggests a potential missed opportunity. The split in responses may be institution specific where some centers have a robust APP research and quality initiative and others have yet to optimize the APP role in this way.…”
Section: Discussionmentioning
confidence: 99%